The Influence of Customer Knowledge Service Quality and Location on Wadiah Savings Customers at PT. LKMS, BMT Almabruk: Pengaruh Kualitas Layanan Costumer Knowledge Dan Lokasi Terhadap Nasabah Tabungan Wadiah pada Pt. LKMS,BMT Almabruk - Ismi Hamdani; Wilda Yanti (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
The Influence of Customer Knowledge Service and Location on Wadiah Savings Customers at PT. LKMS BMT Almabruk Batusangkar. This study aims to determine the influence of Customer Knowledge Service and Location on Wadiah Savings Customers at PT. LKMS BMT Almabruk Batusangkar. This study is a field study with a quantitative approach. The population in this study were customers of PT. LKMS BMT Almabruk Batusangkar totaling 257 people with a sample of 72 people. Data collection techniques used questionnaires and questionnaires. Data analysis used is quantitative data analysis which means using numbers to analyze data. The data obtained will be processed using SPSS version 22. The results of the study are that Customer Knowledge Service (X1) has a significant effect on Wadiah Savings Customers (Y) at PT. LKMS BMT Al-Mabruk Batusangkar. This is proven by the t-value of the Customer Knowledge Service variable (X1) of 3,950 and the t-table value of 1,667 (0.05: df = n -k -1, df = 72 - 3 - 1 = 68). Customer Knowledge Service (X1) partially influences Wadiah Savings Customers (Y). Location (X2) has a significant effect on Wadiah Savings Customers (Y) at PT. LKMS BMT Al-Mabruk Batusangkar. This is proven by the t-value of the Location variable (X2) of 4,271 and the t-table value of 1,667 (0.05: df = n - k -1, df = 72 - 3 - 1 = 68). Location (X2) partially influences Wadiah Savings Customers (Y). Customer Knowledge Service (X1) and Location (X2) influence Wadiah Savings Customers (Y) at PT. LKMS Al-Mabruk Batusangkar. This is proven by the F count of 23,543 with a significance of 0.000. It can be seen in the statistical table at a significance level of 0.05 with df 2 (number of variables - 1) = 1 and df 2 (n-k-1) or (72-3-1) = 68 with n is the number of data and k is the number of variables where the results obtained for the F table are 3.13. It can be concluded that the F count> F table (23,543> 3.13) and the significance <0.05 is (0.00 <0.05). This means that Customer Knowledge Services (X1) with Location (X2) together have an influence on Wadiah Savings Customers (Y).